Hållbarhetsprincipen i artikel 18.2 i direktiv 2014/24/EU – En princip som alla andra? Ett skandinaviskt perspektiv - Myrann Lavesson,Vilma (2024)
Public procurement is regulated at EU level by e.g. Directive 2014/24/EU. The Directive enabled Member States to consider the environment to a greater extent in public procurement. In line with this, the Court of Justice of the EU established, in the case Tim, that there is a principle of sustainability in Article 18(2) of the Directive, and this principle is equivalent to the traditional procurement principles in Article 18(1). The principles in Article 18(1) have a twofold function. On the one hand, they serve as a benchmark for the interpretation of the other provisions of the Directive and, on the other hand, they create rights and obligations beyond what is explicitly stated in the Directive. The question is whether the principle of sustainability in Article 18(2), considering the Tim case, has the same dual function and, by extension, whether Sweden's implementation of Article 18(2) is satisfactory. In Sweden, the “should-rule” (bör-regeln) in Chapter 4 Section 3 of the Public Procurement Act (lag (2016:1145) om offentlig upphandling) implements Article 18(2) of the Directive. The should-rule is, as the name suggests, not binding on contracting authorities. The purpose of this essay was to investigate whether this implementation is in accordance with the underlying EU law, or if it is required that Sweden changes the regulations. To this end, the interpretation and implementation of Article 18(2) by our Scandinavian neighbours was also examined. Therefore, both the legal dogmatic and the comparative method were applied in the essay. The possible second function of the sustainability principle – to give rise to rights and obligations – is still unclear. In relation to Norway and Denmark, it was established that Sweden has chosen a middle way. Finally, it was noted that, to ensure a loyal implementation of EU law, Sweden should change the wording of the should-rule to make it clearer that the rule constitutes a principle.
Keywords: EU-rätt; komparativ rätt; offentlig upphandling